Prevalence of Giardia Lamblia in Stool Samples of Diarrhea Patients in Khost, Afghanistan - Nekmal, Tahir Shah; Jan, Rauf (Integrated Journal for Research in Arts and Humanities, 2023)
The present study was conducted in khost post graduate civil hospital to determine the prevalence of Giardia lambalia in stool samples of patients with complain of diarrhea or abdominal discomfort which were came from center and others different districts of Khost province. Three hundred sixty-eight (368) fecal samples were collected randomly from the male, female and children patients who visited OPD (outpatient department) of mention hospitals from March 2022 to August 2022. The samples were screened for the presence of parasites using microscopic techniques (formalin ethyl acetate sedimentation technique). Out of 368 sample analyzed protozoa etiological agent Giardia lambalia was detected in 34 (9.2%) which were representative of total population. Regarding sex in male 25(70%) and 9(30%) were female positive were detected. To control Giardia lamblia is by good hygiene, adequate cooking of food, and protection of food from flies, properly wash raw vegetables before serving, use of boiled water and well developed sewage system. The study concluded that the use of raw animal manure for fertilizer, irrigation of vegetables with fecal contaminated water, poor sanitary system and improper treatment of water supplies can increase the threat of contamination of water which is main source of causing giardiasis and other infections.